A comparative study on electrothermal characteristics of nanoscale multiple gate MOSFETs. (November 2017) - Gu, Qi-Lin; Zhang, Peng; Ru, Yi; Song, Hao; Zhao, Wen-Sheng; Yin, Wen-Yan
Abstract: Multiple-gate (MG) MOSFETs are promising candidates for next-generation integrated circuits technology. This paper presents the electrothermal characterization of three-type nanoscale MG MOSFETs, i.e., Π-gate, quadruple-gate (QG), and Ω-gate MOSFETs. Meanwhile, the temperature distribution of a real Ω-gate MOSFET with gradual channel width is also studied. Finite difference method (FDM) is adopted to solve the 3-D time-dependent heat conduction equations. The simulation results of the steady-state temperature distribution are validated against the commercial software COMSOL. Moreover, the transient temperature response of MG MOSFETs to different waveforms are also captured and compared.